Can we count on early numerical abilities for early probabilistic reasoning abilities?. Issue 1 (2nd January 2022) - Supply, Anne-Sophie; Van Dooren, Wim; Onghena, Patrick
ABSTRACT: Previous research has shown that early numerical abilities are predictive of later mathematical achievement. In line with these previous studies, we investigated whether early numerical abilities are also associated with later probabilistic reasoning abilities. In the present study, we examined children's numerical abilities in the second grade of preschool and their probabilistic reasoning abilities one and two years later. On the one hand, our results indicate that early numerical abilities assessed in the second grade of preschool predict the use of erroneous solving strategies to compare probabilities and create equal probabilities in the third grade of preschool. On the other hand, our results also indicate that the same early numerical abilities predict the use of more advanced or correct strategies when children are in the first grade of primary school. We discuss these seemingly contradicting findings in light of current research on probabilistic reasoning abilities.